CocoCloud Bites by Cocolab / Nur'Saffiya Edriana Radzuan ... [et al.] - Radzuan, Nur'Saffiya Edriana; Zakaria, Nur Aida Shafiza; Mohd Ishadi, Nur Aqilah; Hassim, Nur Syuhadah; Rasid, Siti Aishah (2024)
Brief description of the business and product concepts, CocoLab was established in January 2024 by Miss Nur Syuhadah Hassim, and it is a company that manufactures nougat using coconut dregs to decrease waste as one of the components in their main confectionary product, CocoCloud Bites. The firm is co-owned and managed by five (5) devoted partners from varied backgrounds, with each of us holding managerial roles in the company. Cocolab takes a unique approach to nougat manufacture by integrating coconut dregs, solving the pressing issue of food waste in a tasty and ecological way. Coconut dregs, a byproduct of coconut processing, are sometimes disregarded, but Cocolab has harnessed their potential to produce a unique and environmentally beneficial nougat. CocoCloud Bites not only fulfil the sweet desires but also help to reduce food waste, making it an ecologically conscientious decision. One-bite size signifies a dedication to neutralising food waste by repurposing wasted coconut dregs into a tasty, guilt-free snack. CocoCloud Bites combines convenience with mindful consumption, providing a moment of pure enjoyment that aligns with the concept of responsible indulgence. Every reason to appreciate CocoCloud Bites, from the rich texture to the tropical hints, is encompassed in a single, delightful bite. The target market and projections, CocoCloud Bite's target market consists of students, working people, and the public aged 18 to 55. Due to CocoCloud Bites being sliced into bite-sized pieces, they are easy to share with friends or classmates at a reasonable price and this might be a pleasant and social aspect of snacking, promoting a sense of community.